Variability of Soil Hydrophysical Parameters in Different Geomorphological Conditions of the Subboreal Zone of the Chuvash Republic - Vasyukov Sergey; Iakimovich Dmitrii; Sirotkin Vyacheslav; Usmanov Bulat (BIO Web of Conferences)
This paper analyses the hydrophysical parameters of soils and their variability, as well as soil moisture availability in relation to their geomorphological conditions in the subboreal zone of the Chuvash Republic. The research was carried out at three polygons, each including several sampling points in different geomorphological conditions. The authors analysed a number of indicators, including soil volume mass, solid phase density, soil porosity, soil filtration coefficient, specific volume surface of solid phase and soil moisture potential. The aforementioned data were used to construct basic hydrophysical characteristic (BHC) curves for each site. It was then possible to draw conclusions regarding the existence of notable changes in soil moisture availability for plants and soil hydrophysical properties in response to changes in absolute altitude and geomorphological conditions, as well as in relation to soil type.